Stability Analysis of Open Pit Mine Slopes Case Study: Nalou Open Pit Mine, Sepon Gold Mine, Vilabouly District, Savannakhet Province, Lao PDR - Pongpanya, Phanthoudeth (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
Slope stability analysis is a crucial and necessary component in the design and planning of open-pit mining operations. It involves assessing the likelihood of slope failure during mining activities to enable the implementation of appropriate mining methods and preventive measures, thereby ensuring safety and minimizing potential losses due to slope instability. This study analyzes the slope stability of the Nalu Open Pit Mine, located within the Sepon Gold Mine in Vilabuly District, Savannakhet Province, Lao PDR. The analysis utilizes the Slope W/2012 program for numerical simulation and considers a Factor of Safety (FoS) greater than 1.200 as the threshold for slope stability. The slope stability assessment was conducted across five sections Sections 1, 2, 3, 4, and 6 under two conditions: with and without the influence of groundwater. The results indicate that the pit slopes are stable when groundwater effects are not considered, with FoS values of 2.047, 1.562, 1.802, 1.732, and 2.012 for Sections 1, 2, 3, 4, and 6, respectively. However, when groundwater effects are taken into account, the FoS values decrease significantly to 1.480, 1.213, 1.362, 1.263, and 1.523 for the same respective sections. Despite the reduction in stability, all slopes remain stable under the defined criteria, even with the influence of groundwater.